The Effects of Forodesine in Murine and Human Multiple Myeloma Cells - Liesbeth Bieghs; Jo Caers; Elke De Bruyne; Els Van Valckenborgh; Fiona Higginbotham; Karin Vanderkerken; Eline Menu (Advances in Hematology)
Multiple myeloma (MM) is the second most commonly diagnosed hematological malignancy, characterized by a monoclonal proliferation of malignant cells in the bone marrow. Despite recent advances in treatment strategies, MM remains incurable and new therapeutical targets are needed. Recently forodesine, a purine nucleoside phosphorylase inhibitor, was found to induce apoptosis in leukemic cells of chronic lymphocytic leukemia patients by increasing the dGTP levels. We therefore tested whether forodesine was able to inhibit proliferation and/or induce apoptosis in both murine and human MM cells through a similar pathway. We found that after 48 hours of treatment with forodesine there was a slight dGTP increase in 5T33MM and RPMI-8226 MM cells associated with partial inhibition of proliferation and a limited induction of apoptosis. When investigating the pathways leading to cell cycle arrest and apoptosis, we observed an upregulation of p27, caspase 3, and BIM. We can conclude that forodesine has some effects on MM cells but not as impressive as the known effects in leukemic cells. Forodesine might be however potentiating towards other established cytotoxic drugs in MM.